The Description Of Participants' Interest To Successfully Get A Competence Certification at LKP Evi Salon Kota Pariaman - Diana Rahmi; Alim Harun Pamungkas (Universitas Negeri Padang, 2022)
This research was motivated by the high interest of the trainees in successfully obtaining competency certification at the Evi salon training and course institution in Pariaman City, their enthusiasm for learning in training and the activeness of the trainees in the learning process. Allegedly caused by the skills of learning resources/instructors, interesting material was delivered by the instructor during the learning process. This type of research is quantitative descriptive research. The population in this study were 40 people who attended training at the Evi Salon Kota Pariaman training and training institute in 2018 and 2019 and the research sample consisted of 20 people. The data collection technique used a questionnaire, with a questionnaire sheet collection tool, and the data analysis technique used the percentage formula. It is highly recommended that the organizer or manager should be able to adjust and improve the needs of the training participants, so that the training can run well and smoothly. Learning resources/instructors to improve the appearance and use of learning media, so as to create a more intimate and motivated atmosphere in training. Training participants are able to take advantage of the knowledge and skills provided by the instructor and continue to apply and develop them in their daily lives.Keywords: Interests, Training, Competency Certification, Learning Implementation, Success, LKP